Preparation method of crude oil pretreatment demulsifier

By nano-normalizing and surface-treating feather fibers and compounding with silica sol, an efficient crude oil pretreatment deemulsion was prepared, which solved the problems of poor stability, heavy environmental burden and high cost in the prior art, and achieved efficient, economical and environmentally friendly deemulsion effect.

CN119662303AActive Publication Date: 2025-03-21ZIBO KAIMEIKE IND & TRADE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510168899.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-21
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

Existing crude oil demulsants have problems such as poor stability, heavy environmental burden and difficult cost control, especially when dealing with different types of crude oil, the demulsification effect is poor, and the copolymers are difficult to degrade, which may cause potential harm to the environment.

Method used

A crude oil pretreatment deemulsant was prepared by nano-sized and surface-treated to form hydrophilic modified nano-feather fibers and compounded with tetraethoxysilane silica sol. This method enhances the specific surface area and hydrophilicity of nanofeather fibers, combines the formation of silica networks, and improves the dispersion and interface activity of the demulsifier, thereby achieving efficient demulsification.

Benefits of technology

This method achieves efficient demulsification of demulsifiers, good stability and economical and environmentally friendly, and is suitable for the treatment of different types of crude oil, reducing production costs and reducing negative impacts on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a crude oil pretreatment demulsifier, and belongs to the technical field of oilfield chemical engineering, and the crude oil pretreatment demulsifier comprises the following steps: S1, cutting feather fibers into small sections, carrying out ball milling treatment to obtain nano feather fibers, carrying out surface treatment with hydrofluoric acid, immersing the nano feather fibers subjected to surface treatment into a hydrogen peroxide solution, heating and stirring, and carrying out vacuum drying to obtain a crude oil pretreatment demulsifier; hydrophilic modified nano feather fibers are obtained; and S2, mixing tetraethoxysilane with ethanol, adjusting the pH value to 7-9, stirring at normal temperature to generate silica sol, immersing the hydrophilic modified nano feather fibers into the silica sol, continuously stirring, drying and curing to obtain the crude oil pretreatment demulsifier. The crude oil pretreatment demulsifier provided by the invention realizes the purpose of efficient demulsification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemical industry, and in particular to a method for preparing a crude oil pretreatment demulsifier. Background Art

[0002] During the extraction, transportation and processing of crude oil, it is mixed with formation water or injection water and subjected to external mechanical forces (such as pumping, stirring, etc.), which easily forms a stable water-in-oil (W / O) or oil-in-water (O / W) emulsion. This emulsion is usually composed of crude oil, water, emulsifiers (such as natural surfactants, clay particles, etc.) and mechanical impurities. The stability of the emulsion mainly comes from the existence of the interfacial film. This membrane structure is formed by the adsorption of natural emulsifiers (such as asphaltene and colloid) on the oil-water interface and has high mechanical strength and elasticity. The water, inorganic salts and mechanical impurities in the emulsion increase the water content of crude oil, reduce the purity of crude oil, affect the efficiency of subsequent refining processes, and accelerate the corrosion of pipelines and equipment, resulting in increased operating costs of oil fields and refineries.

[0003] Crude oil demulsifiers are a type of chemical agent that acts on crude oil emulsions through physical and chemical means to break the interfacial membrane of the emulsion and quickly separate the oil and water. Common crude oil demulsifiers are divided into non-ionic demulsifiers, cationic demulsifiers, anionic demulsifiers and zwitterionic demulsifiers, but they generally have problems such as poor stability, heavy environmental burden and difficult cost control.

[0004] A demulsifier is disclosed in the patent document with the announcement number CN114736337B. The demulsifier is a copolymer of vinyl aromatic hydrocarbons, long-chain α-olefins and allyl alcohol polyethers. The molar ratio of vinyl aromatic hydrocarbon monomers, α-olefin monomers and allyl alcohol polyether monomers in the copolymer is 1:1:(0.8-1.2), and the number average molecular weight of the polymer is 4000-7000. It is prepared by free radical initiated monomer polymerization. The demulsifier prepared in the patent document has strong selectivity and has a high demulsification efficiency when applied to heavy oil treatment. However, the demulsification effect is reduced when it is used for other crude oil treatment, and the copolymer is difficult to degrade in the natural environment, which is prone to potential environmental problems. In addition, the preparation cost of this demulsifier is also high.

[0005] Therefore, it is necessary to provide a method for preparing a crude oil pretreatment demulsifier to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing a crude oil pretreatment demulsifier, which can achieve the purpose of efficient demulsification, good stability, economy and environmental protection.

[0007] The specific scheme of the present invention is as follows: a method for preparing a crude oil pretreatment demulsifier comprises the following steps: Step S1, cutting feather fibers into small segments, ball-milling to obtain nano-feather fibers, and then surface-treating the nano-feather fibers with hydrofluoric acid, immersing the surface-treated nano-feather fibers in a hydrogen peroxide solution, heating and stirring to obtain hydrophilically modified nano-feather fibers; Step S2, tetraethoxysilane is mixed with ethanol, the pH is adjusted to 7-9, and the mixture is stirred at room temperature to generate silica sol, and the hydrophilic modified nano-feather fiber is immersed in the silica sol, the mixture is continuously stirred, and the mixture is dried and solidified to obtain a crude oil pretreatment demulsifier.

[0008] Feather fiber is a natural, high-molecular material with a porous structure, and its main component is keratin. Keratin contains a large number of polar groups (such as carboxyl, amino and thiol), which can provide adsorption sites in emulsified crude oil, so that feather fibers can form stable adsorption at the oil-water interface, which helps the demulsifier to interact with the oil-water interface and weaken the strength of the interfacial film, thereby achieving a demulsification effect.

[0009] The feather fiber after nano-treatment has a larger specific surface area, which can increase the interface in contact with the emulsion and improve the demulsification efficiency. The surface of the nano-feather fiber is roughened by hydrofluoric acid treatment to increase the roughness of the surface of the nano-feather fiber, thereby enhancing the physical and chemical interaction between the nano-feather fiber and the oil-water interface. The surface roughening treatment significantly increases the specific surface area of ​​the nano-feather fiber, providing more adsorption sites, which is beneficial to the distribution of the demulsifier at the oil-water interface. The roughened surface increases the van der Waals force and capillary force on the interface through microstructures (such as holes and protrusions), enhances the nano-feather fiber's ability to capture the emulsion interface, and achieves efficient demulsification. The rough surface can also physically weaken the integrity of the emulsion interface film, accelerate the stratification of the emulsion, and achieve the purpose of demulsification. Hydrogen peroxide is then used to modify the nano-feather fibers to make them hydrophilic. The strong oxidizing property of hydrogen peroxide can increase the number of carboxyl groups, hydroxyl groups and other polar groups on the surface of the nano-feather fibers. These groups can form hydrogen bonds with water molecules, thereby increasing the hydrophilicity of the nano-feather fibers. After the hydrophilicity is enhanced, the nano-feather fibers can adsorb water phase molecules faster, increase the mutual collisions between dispersed phase droplets, promote the aggregation and fusion of water droplets in the emulsion, form larger droplets, accelerate oil-water separation, and achieve demulsification.

[0010] Through the solution gel method, tetraethoxysilane is used to prepare silica sol, and the hydrophilically modified nano-feather fiber is compounded with silica sol to form a demulsifier with high surface energy and structural stability, thereby improving the processing capacity of crude oil emulsion. Tetraethoxysilane in silica sol is hydrolyzed to form silanol, which is further polycondensed to obtain silicon oxygen bonds to form a silica network, which is then formed into a composite material with nano-feather fibers to obtain a crude oil pretreatment demulsifier, which helps the demulsifier maintain structural stability in complex environments (such as high temperature and high pressure) and avoids the demulsifier from failing during the oil-water separation process. In addition, the silica network can further increase the surface energy, allowing the demulsifier to spread rapidly at the oil-water interface, promote the reduction of interfacial tension, help destroy the stability of the oil-water interface film, and achieve efficient and rapid demulsification. After the silica network is combined with the surface of the nano-feather fiber, the advantages of both are combined. The nano-feather fiber provides multiple adsorption sites, and the silica network enhances the dispersibility and interfacial activity of the demulsifier, thereby significantly improving the demulsification efficiency.

[0011] Feather fiber is a natural waste with low cost. It can be used to prepare demulsifiers after simple treatment, which greatly reduces the production cost. In addition, the demulsifier formed by the composite of natural fiber and silica sol is environmentally friendly, not easy to cause secondary pollution, and significantly reduces the negative impact on the environment.

[0012] Preferably, in step S1, the ball milling speed is 1000-1200 r / min, the time is 3-4 h; and the concentration of the hydrogen peroxide solution is 3-5 wt %.

[0013] Preferably, the surface treatment comprises the following steps: immersing the nano-feather fiber in a hydrofluoric acid solution, reacting at 30-40° C. for 30-60 min, filtering, washing with deionized water, and drying.

[0014] Preferably, the concentration of the hydrofluoric acid solution is 0.09-0.11 wt %. Preferably, in step S1, the heating and stirring speed is 400-500 r / min, the time is 30-50 min, and the temperature is 50-60°C.

[0015] Preferably, in step S2, nano-tungsten carbide is added before stirring at room temperature.

[0016] Nano-tungsten carbide has high hardness and wear resistance, which can improve the durability of demulsifiers in high shear environments and extend their service life. Nano-tungsten carbide also has good chemical inertness and thermal stability, which can improve the applicability of demulsifiers and help maintain the stability of demulsifiers. In addition, nano-tungsten carbide can also cooperate with the porous structure of nano-feather fibers to further increase the specific surface area of ​​the demulsifier, provide more adsorption sites, enhance the interface adsorption capacity, and improve the demulsification efficiency.

[0017] Preferably, in step S2, the stirring speed at room temperature is 300-500 r / min, and the time is 1-2 h; the continuous stirring speed is 200-300 r / min, and the time is 2-3 h, and the temperature is 30-40°C.

[0018] Preferably, in step S2, the drying temperature is 50-60°C and the time is 10-12 hours; the curing temperature is 120-130°C and the time is 2-3 hours.

[0019] Preferably, the following components are included in parts by weight: 2-3 parts of hydrophilic modified nano feather fibers, 10-15 parts of tetraethoxysilane, 30-40 parts of ethanol, 5-10 parts of deionized water and 1-2 parts of ammonia water.

[0020] Preferably, the demulsifier further comprises 0.5-2 parts of nano-tungsten carbide; The raw materials of the hydrophilic modified nano feather fiber include 4-6 parts of feather fiber, 50-60 parts of hydrofluoric acid solution and 40-50 parts of hydrogen peroxide solution.

[0021] The above technical solution of the present invention includes at least the following beneficial effects: (1) Feather fiber is a natural polymer material whose main component is keratin. It contains polar groups. After nano-scaling, the specific surface area increases, which can provide adsorption sites at the oil-water interface, weaken the interfacial film strength, and improve the demulsification efficiency.

[0022] (2) The surface of the nano-feather fiber is roughened by hydrofluoric acid treatment to increase its specific surface area, provide more adsorption sites, enhance the demulsifier's ability to capture the emulsified interface, weaken the integrity of the interfacial film, accelerate the emulsion stratification, and achieve efficient demulsification.

[0023] (3) Through hydrogen peroxide modification, the carboxyl and hydroxyl groups on the surface of feather fibers increase, the hydrophilicity is significantly improved, the coalescence of water droplets is promoted, the strength of the interfacial film is reduced, and the oil-water separation is accelerated.

[0024] (4) By compounding the modified nano-feather fibers with silica sol, the silica sol hydrolyzes and condenses on the surface of the modified nano-feather fibers to form a silica network. The silica network enhances the dispersibility and interfacial activity of the demulsifier, promotes the reduction of interfacial tension, destroys the stability of the oil-water interface film, and thus improves the demulsification efficiency. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0026] Example 1 Take 6 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1100r / min, grind it for 3.5h, and obtain nano feather fiber. Put the obtained nano feather fiber into 55 parts of 0.1wt% hydrofluoric acid solution, control the temperature at 35℃, keep the reaction time for 50min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 45 parts of 4.5wt% hydrogen peroxide solution, stir it at 300r / min at 50℃ for 50min, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0027] Mix 15 parts of tetraethoxysilane and 40 parts of ethanol evenly, slowly add 10 parts of deionized water and 2 parts of ammonia water, adjust the solution pH to 7-9, add 1.5 parts of nano-tungsten carbide, react for 1.5 hours at 400r / min stirring conditions to obtain a stable silica sol. Immerse 3 parts of hydrophilic modified nano-feather fibers in the silica sol, stir at 250r / min for 3 hours at 30°C, take out and dry at 50°C for 12 hours, and further cure the dried sample at 120°C for 3 hours to obtain a crude oil pretreatment demulsifier.

[0028] Example 2 Take 5 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1000r / min, grind it for 4h, and obtain nano feather fiber. Put the obtained nano feather fiber into 55 parts of 0.1wt% hydrofluoric acid solution, control the temperature at 40℃, keep the reaction time for 30min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 40 parts of 3.5wt% hydrogen peroxide solution, stir it at 350r / min at 55℃ for 40min, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0029] 12 parts of tetraethoxysilane and 35 parts of ethanol were mixed evenly, 5 parts of deionized water and 1.5 parts of ammonia water were slowly added, the pH of the solution was adjusted to 7-9, and the reaction was carried out under stirring conditions of 500r / min for 1h to obtain a stable silica sol. 2 parts of hydrophilic modified nano-feather fibers were immersed in the silica sol, stirred at 200r / min for 2h at 30°C, taken out and dried at 60°C for 10h, and the dried sample was further cured at 130°C for 2h to obtain a crude oil pretreatment demulsifier.

[0030] Example 3 Take 6 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1200r / min, grind it for 3h, and obtain nano feather fiber. Put the obtained nano feather fiber into 60 parts of 0.09wt% hydrofluoric acid solution, control the temperature at 30℃, keep the reaction time for 60min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 42 parts of 5wt% hydrogen peroxide solution, stir it at 400r / min for 35min at 60℃, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0031] Mix 15 parts of tetraethoxysilane and 40 parts of ethanol evenly, slowly add 8 parts of deionized water and 2 parts of ammonia water, adjust the solution pH to 7-9, add 0.5 parts of nano-tungsten carbide, and react for 1.5 hours at 300r / min stirring to obtain a stable silica sol. Immerse 3 parts of hydrophilic modified nano-feather fibers in the silica sol, stir at 250r / min at 40°C for 2.5 hours, take out and dry at 55°C for 11 hours, and further cure the dried sample at 125°C for 2.5 hours to obtain a crude oil pretreatment demulsifier.

[0032] Example 4 Take 4 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1050r / min, grind it for 3.5h, and obtain nano feather fiber. Put the obtained nano feather fiber into 50 parts of 0.09wt% hydrofluoric acid solution, control the temperature at 35℃, keep the reaction time for 45min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 50 parts of 3.5wt% hydrogen peroxide solution, stir it at 350r / min for 30min at 60℃, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0033] 10 parts of tetraethoxysilane and 30 parts of ethanol were mixed evenly, 7 parts of deionized water and 1 part of ammonia water were slowly added, the pH of the solution was adjusted to 7-9, and the reaction was carried out at 350r / min for 1.5 hours to obtain a stable silica sol. 2.5 parts of hydrophilic modified nano-feather fibers were immersed in the silica sol, stirred at 300r / min for 2 hours at 35°C, and then taken out and dried at 60°C for 11 hours. The dried sample was further cured at 130°C for 2 hours to obtain a crude oil pretreatment demulsifier.

[0034] Example 5 Take 5 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1150r / min, grind it for 3h, and obtain nano feather fiber. Put the obtained nano feather fiber into 50 parts of 0.1wt% hydrofluoric acid solution, control the temperature at 40℃, keep the reaction time for 55min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 48 parts of 3wt% hydrogen peroxide solution, stir it at 400r / min for 40min at 50℃, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0035] Mix 15 parts of tetraethoxysilane and 35 parts of ethanol evenly, slowly add 6 parts of deionized water and 1.5 parts of ammonia water, adjust the solution pH to 7-9, add 2 parts of nano-tungsten carbide, and react for 2 hours at 300r / min stirring to obtain a stable silica sol. Immerse 2 parts of hydrophilic modified nano-feather fibers in the silica sol, stir at 200r / min for 3 hours at 40°C, take out and dry at 50°C for 12 hours, and further cure the dried sample at 120°C for 2.5 hours to obtain a crude oil pretreatment demulsifier.

[0036] Example 6 Take 6 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1100r / min, grind it for 3.5h, and obtain nano feather fiber. Put the obtained nano feather fiber into 60 parts of 0.11wt% hydrofluoric acid solution, control the temperature at 30℃, keep the reaction time for 35min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 45 parts of 4.5wt% hydrogen peroxide solution, stir it at 300r / min at 55℃ for 50min, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0037] 12 parts of tetraethoxysilane and 40 parts of ethanol were mixed evenly, 9 parts of deionized water and 2 parts of ammonia water were slowly added, the pH of the solution was adjusted to 7-9, and the reaction was carried out at 450r / min for 1h to obtain a stable silica sol. 3 parts of hydrophilic modified nano-feather fibers were immersed in the silica sol, stirred at 300r / min for 2h at 30°C, taken out and dried at 60°C for 10h, and the dried sample was further cured at 130°C for 2h to obtain a crude oil pretreatment demulsifier.

[0038] Example 7 Take 4 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1200r / min, grind it for 3h, and obtain nano feather fiber. Put the obtained nano feather fiber into 55 parts of 0.11wt% hydrofluoric acid solution, control the temperature at 35℃, keep the reaction time for 50min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 40 parts of 4wt% hydrogen peroxide solution, stir it at 350r / min for 40min at 60℃, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0039] 10 parts of tetraethoxysilane and 30 parts of ethanol were mixed evenly, 10 parts of deionized water and 2 parts of ammonia water were slowly added, the pH of the solution was adjusted to 7-9, and 1 part of nano-tungsten carbide was added, and the reaction was carried out at 400r / min stirring conditions for 1.5 hours to obtain a stable silica sol. 2.5 parts of hydrophilic modified nano-feather fibers were immersed in the silica sol, stirred at 250r / min at 35°C for 2.5 hours, taken out and dried at 50°C for 11 hours, and the dried sample was further cured at 125°C for 2 hours to obtain a crude oil pretreatment demulsifier.

[0040] Example 8 Take 4 parts of feather fiber, place it in deionized water, add neutral detergent, clean and remove surface dirt and grease, rinse with deionized water several times, and dry. Cut the dried feather into small pieces, put it into a high-energy ball mill, set the speed to 1200r / min, grind it for 3h, and obtain nano feather fiber. Put the obtained nano feather fiber into 55 parts of 0.11wt% hydrofluoric acid solution, control the temperature at 35℃, keep the reaction time for 50min, filter it after the reaction, wash it with deionized water until neutral, and dry it to obtain surface-treated nano feather fiber. Add the surface-treated nano feather fiber to 40 parts of 4wt% hydrogen peroxide solution, stir it at 350r / min for 40min at 60℃, filter it, wash it, and dry it to obtain hydrophilic modified nano feather fiber.

[0041] 10 parts of tetraethoxysilane and 30 parts of ethanol were mixed evenly, 10 parts of deionized water and 2 parts of ammonia water were slowly added, the pH of the solution was adjusted to 7-9, and the reaction was carried out at 400r / min for 1.5 hours to obtain a stable silica sol. 2.5 parts of hydrophilic modified nano-feather fibers were immersed in the silica sol, stirred at 250r / min for 2.5 hours at 35°C, and then taken out and dried at 50°C for 11 hours. The dried sample was further cured at 125°C for 2 hours to obtain a crude oil pretreatment demulsifier.

[0042] The present invention also carries out comparative examples and related tests.

[0043] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that hydrophilic modified nano feather fibers are not prepared, and other compositions and preparation methods are the same as those of Example 1.

[0044] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that tetraethoxysilane is not used to prepare the silica sol, and other compositions and preparation methods are the same as those of Example 1.

[0045] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that hydrofluoric acid is not used to perform surface treatment on the nano-feather fibers, and other compositions and preparation methods are the same as those of Example 1.

[0046] Performance testing Demulsifiers prepared in Examples 1-8 and Comparative Examples were used for demulsification tests. The crude oil emulsion used was a water-in-oil type crude oil emulsion with a water content of 30%, and the mass volume ratio of the demulsifier to the crude oil emulsion was 600 mg / L. The test method was based on SY / T5281-2000 "Test Method for Performance of Crude Oil Demulsifier (Bottle Test Method)", and the demulsification test was carried out at room temperature and 65°C for 60 minutes. The results are shown in Table 1.

[0047] Table 1

[0048] According to the data in Table 1, compared with Example 1, the demulsifier prepared in Comparative Example 1 did not prepare hydrophilic modified nano feather fibers, resulting in the demulsification effect being affected, indicating that hydrophilic modification is conducive to the demulsifier entering the oil-water interface, destroying the stability of the boundary membrane, and improving the demulsification effect of the demulsifier; Compared with Example 1, the demulsification effect of Comparative Example 2 at room temperature is slightly reduced, but the demulsification effect at 65°C is significantly reduced, indicating that the compounding of silica is conducive to improving the demulsification effect of the demulsifier, and can also help the demulsifier to remain stable in a high temperature environment; Comparative Example 3 did not use hydrofluoric acid to surface treat the nano feather fibers. Compared with the demulsifier prepared in Example 1, the demulsification effect has a certain gap, indicating that the hydrofluoric acid surface treatment can roughen the surface of the nano feather fibers, which is helpful for the demulsifier to destroy the integrity of the interface membrane, promote emulsion stratification, and achieve efficient demulsification.

[0049] Compared with Example 7, Example 8 did not add nano-tungsten carbide in the preparation of silica sol, resulting in the demulsification effect of the prepared demulsifier being lower than that of Example 7, especially in an environment of 65°C, the decrease is more obvious, indicating that nano-tungsten carbide is beneficial to improving the demulsification efficiency of the demulsifier in a higher temperature environment, and can also improve the adsorption effect of the demulsifier on the interfacial film.

[0050] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing a crude oil pretreatment demulsifier, characterized in that: The following steps are involved: Step S1, cutting feather fibers into small segments, ball-milling to obtain nano-feather fibers, and then surface-treating the nano-feather fibers with hydrofluoric acid, immersing the surface-treated nano-feather fibers in a hydrogen peroxide solution, heating and stirring to obtain hydrophilically modified nano-feather fibers; Step S2, tetraethoxysilane is mixed with ethanol, the pH is adjusted to 7-9, and the mixture is stirred at room temperature to generate silica sol, and the hydrophilic modified nano-feather fiber is immersed in the silica sol, the mixture is continuously stirred, and the mixture is dried and solidified to obtain a crude oil pretreatment demulsifier.

2. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: In the step S1, the ball milling speed is 1000-1200 r / min, the time is 3-4 h; and the concentration of the hydrogen peroxide solution is 3-5 wt %.

3. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: The surface treatment comprises the following steps: immersing the nano-feather fiber in a hydrofluoric acid solution, reacting at 30-40° C. for 30-60 minutes, filtering, washing with deionized water, and drying.

4. The method for preparing a crude oil pretreatment demulsifier according to claim 3, characterized in that: The concentration of the hydrofluoric acid solution is 0.09-0.11 wt %.

5. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: In step S1, the heating and stirring speed is 400-500 r / min, the time is 30-50 min, and the temperature is 50-60°C.

6. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: In the step S2, nano tungsten carbide is added before stirring at room temperature.

7. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: In step S2, the stirring speed at room temperature is 300-500 r / min, and the time is 1-2 h; the continuous stirring speed is 200-300 r / min, and the time is 2-3 h, and the temperature is 30-40°C.

8. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: In step S2, the drying temperature is 50-60°C for 10-12 hours; the curing temperature is 120-130°C for 2-3 hours.

9. The method for preparing a crude oil pretreatment demulsifier according to claim 1, characterized in that: The composition comprises the following components in parts by weight: 2-3 parts of hydrophilic modified nano feather fibers, 10-15 parts of tetraethoxysilane, 30-40 parts of ethanol, 5-10 parts of deionized water and 1-2 parts of ammonia water.

10. The method for preparing a crude oil pretreatment demulsifier according to claim 9, characterized in that: The demulsifier also includes 1-2 parts of nano tungsten carbide; The raw materials of the hydrophilic modified nano feather fiber include 4-6 parts of feather fiber, 50-60 parts of hydrofluoric acid solution and 40-50 parts of hydrogen peroxide solution.

Citation Information

Patent Citations

  • A demulsifier, its preparation method and its application

    CN114736337B

  • Use of proteins as demulsifying agents

    CN101151081A

  • Demulsifier and preparation method thereof

    CN109054888A

  • Carbon fiber / nanometer silicon dioxide compound as well as preparation method and application thereof

    CN112210397A

  • Breaker Additives For Extended Delay In Removal Of Oil-Based Filter Cakes

    US20210115319A1